The exosomal protein biomarkers auxiliary in diagnosis of interstitial lung disease - Ming Dong; Gaolei Hu; Xi Chen; Lingling Zhang; Yuxiao Zhang; Yanting Fang; Shuilin Liao; Yukai Wang; Qian Li; Peiyan Zheng; Bingpeng Guo; Tinpou Lai; et al. (Respiratory Research)
Abstract Background Exosome liquid biopsies might be a good supplement for early diagnosis of interstitial lung disease (ILD), especially those challenging cases such as connective tissue disease-ILD (CTD-ILD). Methods We developed a circulating exosomal proteomic signature to identify novel biomarkers of ILDs combined with high-resolution CT (HRCT) examination and a new method that makes exosome testing clinically feasible. Blood-derived exosomes were extracted and characterized using a centrifugal microfluidic disc system (Exo-CMDS)-based chemiluminescence immunoassay before being subjected to proteomic analysis by mass spectrometry. Significantly differentially expressed proteins (DEPs) were identified and validated in > 600 clinical samples (collected at three hospitals) by comparing the ILD and disease/healthy control groups. Multivariable logistic regression (LR) analysis was implemented to test the diagnostic performance of the selected biomarkers either alone or in combination. Results Candidate biomarkers KL-6, CAPN2, SP-B were selected from the top DEPs. An LR model that combined exosomal KL-6/CAPN2/SP-B levels performed well in both the discovery (AUC = 0.987, 95%CI = 0.975–0.998) and validation (AUC = 0.936, 95%CI = 0.911–0.960) sets. The LR model based on the three biomarkers exhibited markedly better diagnostic performance (AUC = 0.880, 95%CI = 0.834–0.925) in serum-KL-6-negative ILD, than the conventional serum-KL-6-based method and could also accurately diagnose connective tissue disease associated-ILD (CTD-ILD) in the context of CTD. Conclusion The circulating exosomal protein detection system used in this study represents a valuable tool for identifying promising exosomal biomarkers for ILD and holds promise for improving the diagnosis and prognosis of patients with ILD in the future.